EVASION FROM IFPE HIGHER COURSES IN THE METROPOLITAN AREA OF THE CITY OF RECIFE: CAUSES AND CONSEQUENCES - Semeão Prazeres, Isaque; de Oliveira Quaresma, Daniel (Revista Gênero e Interdisciplinaridade, 2024)
This research discusses a relevant topic in the educational field: the phenomenon of dropout at the Federal Institute of Education, Science and Technology of Pernambuco, in Campi Recife, Igarassu and Ipojuca. The courses under analysis were the superior ones that started in 2015 and concluded in the first semester of 2019. This being the time frame takes into account the end of a period of growth of these institutions in Brazil as a whole, as well as the beginning of a phase quite challenging. The general objective of the study was to investigate the causes and consequences of dropout in higher education courses at IFPE in the metropolitan area of ​​the city of Recife. The methodology applied was two moments, the first being a cross-sectional bibliographic review of quantitative and retrospective character. For the second moment, using a questionnaire and structured interview, as to the nature, we understand that this investigation is applied, being understood as a case study, and the qualitative approach used, where they addressed the causes and consequences of evasion in the higher education in the metropolitan area of ​​the city of Recife. The investigated public was composed of students (203) and educators (27), from the 10 higher education courses at IFPE, in the Campi mentioned. And, finally, it appears that, given the detailed analysis of the problems of school dropout. For there to be a possible reintegration, both on the part of educators and students, managing the resources of a teaching institution well is essential to optimize the students’ learning.